Melemahnya Citra Merek Global Akibat Fenomena Cancel Culture: Studi pada Starbucks di Rest Area Bogor - Diah Renata Anggraeni; Dina Mayasari Soeswoyo; Anastasya Cecillia De Venus (Yayasan Literasi Sains Indonesia, 2026)
The phenomenon of cancel culture, which has rapidly evolved through social media, has significantly reshaped global consumer behavior, including within the food and beverage industry integrated into the tourism sector. In the context of international social and political conflicts, consumers no longer base their decisions solely on product quality and brand reputation, but also consider moral values, corporate ethics, and digitally constructed public perceptions. This study aims to analyze the influence of brand image on consumer purchase decisions at Starbucks located in the KM45 Ciawi Rest Area following the emergence of global boycott issues. A quantitative approach was employed using a survey method involving 150 respondents selected through accidental sampling. Data were collected through a modified four-point Likert-scale questionnaire and analyzed using validity testing, reliability testing, classical assumption tests, and simple linear regression with SPSS version 26. The findings indicate that brand image has a positive and statistically significant effect on purchase decisions. However, the results also reveal that within the context of cancel culture, the influence of global brand image, while present, is no longer a dominant determinant of consumer purchase decisions in tourism-related areas. The study highlights the importance of adaptive, socially responsive, and value-based branding strategies to ensure the sustainability of food and beverage businesses within the tourism industry.